Efficacy of chestnut and quebracho wood extracts to control Salmonella in poultry - Casanova, Natalia Andrea; Redondo, Leandro Martin; Redondo, Enzo Alejandro; Joaquim, Patricia Estefania; Dominguez, Johana Natali; Fernandez Miyakawa, Mariano Enrique; Chacana, Pablo (Wiley, 2023)
Aims: The study was aimed to evaluate the antibacterial activity and efficacy of chestnut and quebracho wood extracts against Salmonella by in vitro assays and in vivo trials. Methods and results: The extracts showed inhibitory activity against Salmonella determined by the minimum inhibitory concentration method as well as on the adhesion and invasion of S. Gallinarum (SG) and S. Enteritidis (SE) in Caco-2 cells. Also, transmission electron microscopy revealed that extract-treated Salmonella showed disruption of cell walls and membranes, damage of the cytoplasm and tannin-protein aggregations. In addition, efficacy of the extracts to control SG and SE was evaluated in experimental infection trials in laying hens and broilers respectively. SE excretion was significantly reduced on days 5 (P < 0·01) and 12 (P < 0·025) only in the quebracho group. In the fowl typhoid infection model, hens that received the chestnut extract showed a significantly reduced mortality (P < 0·05). Conclusions: Our results evidence that these alternative natural products may be a useful tool to control Salmonella in poultry.